Event-driven management algorithm of an Engineering documents circulation system; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Kuzenkov V. (2015, 2015)
Title screen